Observation of site-selective chemical bond changes via ultrafast chemical shifts - Andre Al-Haddad; Solène Oberli; Jesús González-Vázquez; Maximilian Bucher; Gilles Doumy; Phay Ho; Jacek Krzywinski; Thomas J. Lane; Alberto Lutman; Agostino Marinelli; Timothy J. Maxwell; Stefan Moeller; et al. (Nature Communications, 2022)
X-ray photoelectron spectroscopy probes the chemical environment in a molecule at a specific atomic site. Here the authors extend this concept with a site selective trigger to follow chemical bond changes as they occur on the femtosecond time scale.